Membrane protein retrieval from the Golgi apparatus to the endoplasmic reticulum (ER): characterization of the RER1 gene product as a component involved in ER localization of Sec12p - Sato, K; Nishikawa, S; Nakano, A (Molecular biology of the cell, 1995)
Yeast Sec12p, a type II transmembrane glycoprotein, is required for formation of transport vesicles from the endoplasmic reticulum (ER). Biochemical and morphological analyses have suggested that Sec12p is localized to the ER by two mechanisms: static retention in the ER and dynamic retrieval from the early region of the Golgi apparatus. The rer1 mutant we isolated in a previous study mislocalizes the authentic Sec12p to the later compartments of the Golgi. To understand the role of RER1 on Sec12p localization, we cloned the gene and determined its reading frame. RER1 encodes a hydrophobic protein of 188 amino acid residues containing four putative membrane spanning domains. The rer1 null mutant is viable. Even in the rer1 disrupted cells, immunofluorescence of Sec12p stains the ER, implying that the retention system is still operating in the mutant. To determine the subcellular localization of Rer1p, an epitope derived from the influenza hemagglutinin was added to the C-terminus of Rer1p and the cells expressing this tagged but functional protein were observed by immunofluorescence microscopy. The anti-HA monoclonal antibody stains the cells in a punctate pattern that is typical for Golgi proteins and clearly distinct from the ER staining. This punctate staining was in fact exaggerated in the sec7 mutant that accumulates the Golgi membranes at the restrictive temperature. Furthermore, double staining of Rer1p and Ypt1p, a GTPase that is known to reside in the Golgi apparatus, showed good colocalization. Subcellular fractionation experiments indicated that the fractionation pattern of Rer1p was similar to that of an early Golgi protein, Och1p. From these results, we suggest that Rer1p functions in the Golgi membrane to return Sec12p that has escaped from the static retention system of the ER.